2004
DOI: 10.1111/j.1365-313x.2004.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications and advantages of virus‐induced gene silencing for gene function studies in plants

Abstract: ). † These authors contributed equally to this work. SummaryVirus-induced gene silencing (VIGS) is a recently developed gene transcript suppression technique for characterizing the function of plant genes. The approach involves cloning a short sequence of a targeted plant gene into a viral delivery vector. The vector is used to infect a young plant, and in a few weeks natural defense mechanisms of the plant directed at suppressing virus replication also result in specific degradation of mRNAs from the endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
530
1
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(545 citation statements)
references
References 95 publications
8
530
1
6
Order By: Relevance
“…To date, VIGS has had broad application in dicots (Burch-Smith et al 2004) and has also proven to be feasible in barley when using engineered Barley Stripe Mosaic Virus (BSMV) vectors (Holzberg et al 2002). Using PDS and the visible photobleaching phenotype, Holzberg et al (2002) showed that the BSMV-VIGS system elicits target-directed gene silencing in barley in a sequence dependent manner.…”
Section: Transient Rnai In Wheat Through Virus Induced Gene Silencingmentioning
confidence: 99%
“…To date, VIGS has had broad application in dicots (Burch-Smith et al 2004) and has also proven to be feasible in barley when using engineered Barley Stripe Mosaic Virus (BSMV) vectors (Holzberg et al 2002). Using PDS and the visible photobleaching phenotype, Holzberg et al (2002) showed that the BSMV-VIGS system elicits target-directed gene silencing in barley in a sequence dependent manner.…”
Section: Transient Rnai In Wheat Through Virus Induced Gene Silencingmentioning
confidence: 99%
“…By inducing gene silencing in regenerated plants, it can also bypass the problem of lethality during embryonic development (Robertson, 2004;Burch-Smith et al, 2004). VIGS provides for the rapid reduction, but not elimination, of gene expression by taking advantage of natural PTGS mechanisms used for viral defense.…”
Section: Virus Induced Gene Silencing (Vigs)mentioning
confidence: 99%
“…It is thus fundamentally similar to RNAi technologies . Typically, VIGS vectors include the bulk of the viral genome, but where a sequence of the gene that is the target for silencing has been inserted (Robertson 2004;Burch-Smith et al, 2004). Inoculation with the recombinant virus triggers the plants' silencing machinery, to suppress both the virus and the mRNA of the gene corresponding to the inserted fragment.…”
Section: Virus Induced Gene Silencing (Vigs)mentioning
confidence: 99%
“…RITS is composed by repeat-associated short interfering RNA (rasiRNA) (Meister & Tuschl, 2004); (P) Translational repression of mRNA by miRNP (Meister & Tuschl, 2004 In early approaches on VIGS studies, gene sequences were individually subcloned into viral genomes, and plants were physically inoculated using viral RNA produced by in-vitro transcriptional reactions (Kumagai et al, 1995). The previously described technique is time consuming and produces variable results, only being used when dealing with limited number of genes (Burch-Smith et al, 2004). An easier method for plant infection would be the use of agroinfiltration of viral cloned vectors (Robertson, 2004).…”
Section: Virus Induced Gene Silencing (Vigs)mentioning
confidence: 99%
“…Gene silencing (GS) is defined as a molecular process involved in the down regulation of specific genes, and probably evolved as a genetic defense system against viruses and invading nucleic acids (Brigneti et al, 1998;Voinnet et al, 2000;Waterhouse et al, 2001;Wassenegger, 2002). Currently, there are several routes of GS identified in plants, such as: posttranscriptional gene silencing or RNA interference (PTGS or RNAi) , transcriptional gene silencing , microRNA silencing (Bartel, 2004), and virus induced gene silencing (Burch-Smith et al, 2004). All these pathways play an important role at the cellular level, affecting differentiation, gene regulation (Bartel, 2004), and protection against viruses and transposons (Waterhouse et al, 2001).…”
Section: Introductionmentioning
confidence: 99%